Scientific integrity: critical issues in environmental health research - Merlo Domenico; Knudsen Lisbeth; Vahakangas Kirsi (BMC, 2008)
Abstract Environmental health research is a relatively new scientific area with much interdisciplinary collaboration. Regardless of which human population is included in field studies (e.g., general population, working population, children, elderly, vulnerable sub-groups, etc.) their conduct must guarantee well acknowledged ethical principles. These principles, along with codes of conduct, are aimed at protecting study participants from research-related undesired effects and guarantee research integrity. A central role is attributed to the need for informing potential participants (i.e., recruited subjects who may be enrolled in a study), obtaining their written informed consent to participate, and making them aware of their right to refuse to participate at any time and for any reason. Data protection is also required and communication of study findings must respect participant's willingness to know or not know. This is specifically relevant for studies including biological markers and/or storing biological samples that might be analysed years later to tackle research objectives that were specified and communicated to participants at the time of recruitment or that may be formulated after consent was obtained. Integrity is central to environmental health research searching for causal relations. It requires open communication and trust and any violation (i.e., research misconduct, including fabrication or falsification of data, plagiarism, conflicting interests, etc.) may endanger the societal trust in the research community as well as jeopardize participation rates in field projects.